64.4k views
4 votes
Solve the system of the following equations:

x+3y=-1
2x+2y=6
(-4,1)
(2,-1)
(4,-1)
(5,-2)

2 Answers

1 vote

Answer:


(5, \: - 2)

Explanation:


x + 3y = - 1 \\ 2x + 2y = 6 \\ solve \: the \: equation \\ \\ x = - 1 - 3y \\ 2x + 2y = 6 \\ substitute \: the \: value \: of \: x \: into \: an \\ equation. \\ \\ 2( - 1 - 3y) + 2y = 6 \\ distribute \\ \\ - 2 - 6y + 2y = 6 \\ add \: - 6y \: to \: 2y \\ \\ - 2 - 4y = 6 \\ add \: 2 \: from \: both \: sides \\ \\ - 2y = 8 \\ divide \: both \: sides \: by \: 2 \\ \\ y = - 2 \\ substitute \: the \: value \: of \: y \: into \: an \\ equation. \\ \\ x = - 1 - 3( - 2) \\ distribute \\ \\ - 1 + 6 \\ add \: - 1 \: to \: 6 \\ \\ x = 5 \\ \\ (5, - 2)

User Rgrinberg
by
6.7k points
3 votes
The answer is (5,-2)
User Matt Robertson
by
5.7k points